Influence of saturation degree of metal-hydride cathode on characteristics of penning type ion source of hydrogen - Borisko, V.N.; Klochko, Ye.V.; Sereda, I.N. (Вопросы атомной науки и техники, 2003)
The experimental examinations of Penning type plasma source of hydrogen ions using metal-hydride cathode was carried out. The discharge characteristics, radial distributions of plasma parameters were measured in a gap between the anode and the metal-hydride cathode for different degree of hydrogen saturation of the cathode material. The plasma parameters and voltage drop on the discharge was shown to be depended on the degree of saturation with hydrogen of the metal-hydride cathode. Plasma density on the axis of the system was established to be increased in accordance to the increase of the initial hydrogen saturation of the metal-hydride cathode. This phenomenon is explained by the increase of a desorption intensity of hydrogen from the central part of the surface of the metal-hydride cathode.